Characterization of a glucose- and solvent-tolerant extracellular tannase from Aspergillus phoenicis - Riul, Alana Jacomini [UNESP]; Gonçalves, Heloísa Bressan [UNESP]; Jorge, João Atílio; Guimarães, Luis Henrique Souza (Elsevier, 2013)
Tannases have attracted wider attention because of their biotechnological potential, especially enzymes from filamentous fungi and other microorganisms. However, the biodiversity of these microorganisms has been poorly explored, and few strains were identified for tannase production and characterization. This article describes the production, purification and characterization of a glucose- and solvent-tolerant extracellular tannase from Aspergillus phoenicis. High enzymatic levels were obtained in Khanna medium containing tannic acid up to 72 h at 30 °C under 100 rpm. The purified enzyme with 65% of carbohydrate content had an apparent native molecular mass of 218 kDa with subunits of 120 kDa and 93 kDa and was stable at 50 °C for 1 h. Optima of temperature and pH were 60 °C and 5.0-6.5, respectively. The enzyme was not affected significantly by most ions, detergents and organic solvents. While glucose did not affect the tannase activity, the addition of a high concentration of gallic acid did. The Km values were 1.7 mM (tannic acid), 14.3 mM (methyl-gallate) and 0.6 mM (propyl-gallate). The enzyme was able to catalyze the transesterification reaction to produce propyl-gallate. All biochemical properties suggest the biotechnological potential of the glucose- and solvent-tolerant tannase from A. phoenicis. © 2012 Elsevier B.V. All rights reserved.
Keywords: Aspergillus; Enzyme characterization; Glucose-tolerant enzyme; Organic solvent; Tannase; Aspergillus phoenicis; Biochemical properties; Carbohydrate content; Extracellular; Filamentous fungi; Gallic acids; High concentration; Purified enzyme; Tannic acid; Transesterification reaction; Biodiversity; Biotechnology; Carbohydrates; Characterization; Enzymes; Flavonoids; Microorganisms; Organic solvents; Purification; Soaps (detergents); Solvents; Glucose; detergent; gallic acid methyl ester; gallic acid propyl ester; glucose; organic solvent; tannase; tannin; carbohydrate analysis; carbon source; catalysis; concentration (parameters); culture medium; enzyme activity; enzyme purification; enzyme synthesis; hydrolysis; molecular weight; nonhuman; pH; thermostability; transesterification; Fungi